Multiple detections of insulation defects partial discharge in gas-insulated equipment - Kong, Fanjun; Zhao, Ke; Ma, Jingtan; Zhuang, Tianxin; Li, Hongtao; Gao, Shan; Liu, Jianjun; Zhang, Chaohai (Frontiers in Energy Research, 2022)
Gas-insulated equipment is an important part of the power system owing to its advantages of small footprint, large transmission capacity, and high reliability. Detection of insulation defects partial discharge (PD) is important for its operation and maintenance, and the combination of multiple detection methods can greatly improve the accuracy of PD detection. In this study, the three kinds of insulation defects, namely, floating defect, void defect, and surface defect, are set up on the PD simulation platform and detected using the ultra-high frequency (UHF) method, high-frequency current (HFCT) method, and acoustic emission (AE) method. The partial discharge inception voltage (PDIV) and phase-resolved partial discharge (PRPD) spectrum of defects measured by these three methods are recorded in the experiments. The experimental results show that the UHF method is effective for the detection of the three defects. The HFCT method is sensitive to floating defects but not to void and surface defects. Discharge signals of these two defects can be detected by HFCT when the discharge amplitude is large. The AE method can detect floating defects effectively but cannot detect void defects and surface defects.